HKS Misinfo Review 2022
DOI: 10.37016/mr-2020-102
|View full text |Cite
|
Sign up to set email alerts
|

Audio misinformation on WhatsApp: A case study from Lebanon

Abstract: Since 2019, Lebanon has witnessed sequential crises that have routinely spurred media attention. A great deal of misinformation has proliferated during these events, much of it spreading on WhatsApp. One format is particularly understudied: audio instant messages, otherwise known as voice notes. Utilizing a grounded theory approach to examine 35 misleading WhatsApp voice notes collected between October 2019 and October 2020, this study documents how audio misinformation on Lebanese WhatsApp follows a consisten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…While many features can be derived from text as transcribed voice messages, others are based on the audio modality. Research has found that speech rate and sound volume may be used as an indicator when assessing the credibility of audio material (El-Masri et al, 2022)-an insight we build on in our user study.…”
Section: Audio Featuresmentioning
confidence: 98%
See 3 more Smart Citations
“…While many features can be derived from text as transcribed voice messages, others are based on the audio modality. Research has found that speech rate and sound volume may be used as an indicator when assessing the credibility of audio material (El-Masri et al, 2022)-an insight we build on in our user study.…”
Section: Audio Featuresmentioning
confidence: 98%
“…While we included a broad variety of features on character, word, and sentence level, this selection is not exhaustive and may be extended based on a systematic literature review, especially on the explicit speech modality that may imbue emotions. Existing research indicates that speech rate and sound volume may compose a relevant attribute of voice messages when assessing its credibility (El-Masri et al, 2022). While these features are not yet included in the prototype implementation, they were part of our user study.…”
Section: Computed Featuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, Yaseen and Ali (2022) used discourse analysis to analyze 13 fabricated social media images previously identified by the fact-checking organization Tech4Peace. If we, however, focus on the larger Arab and Middle Eastern context, then we can find more conceptual and empirical studies on misinformation and the reputational attacks against Arab journalists (Al-Rawi 2021a;Bebawi 2022;El-Masri et al 2022;Jones 2021;Mutsvairo and Bebawi 2019) as well as human right activists (Abrahams and Leber 2021;Al-Rawi 2014;Jones 2022). The large majority of the above studies relied on one research method approach, while this paper employs a mixed method approach to identify and analyze disinformation targeting journalists, news organizations, and human rights activists.…”
Section: Introductionmentioning
confidence: 99%